Segregation of effector mechanisms in a tumour-specific CD8+ t-cell clone correlates with CD30 expression - Sun, Yuansheng; Song, Mingxia; Schadendorf, Dirk (Scandinavian journal of immunology, 2001)
In this study we have analyzed CD30-antigen expression in three melanoma-directed cytotoxic T lymphocyte (CTL) clones with a T helper 0 (Th0)-like cytokine secretion profile (i.e. interleukin (IL)-4, IL-5, and interferon (IFN)-γ). We show that all CTL clones expressed high levels of CD30 upon contact with the autologous tumour cells. One CTL clone, termed A2 with a monoclonal feature was selected for further analyses and found its CD30 expression dependent on the presence of IL-4. Functionally, a CD30-expressing A2 CTL was capable of producing higher amounts of IFN-γ (up to 1.5-fold) and IL-4 (up to two-fold) than its CD30− counterpart. Furthermore, CD30-positive A2 CTL displayed an at least three-fold greater proliferative response to the tumour cell stimulation, contrasting with CD30− CTL. However, the antitumour cytotoxic activity of A2 CTL was not modulated by the CD30 expression. These results suggest that CD30 antigen can be inducible on a subset of tumour-directed CD8+ CTL, and that this subset of cells may have profound effector functions, such as cytokine secretion, proliferation, and cytotoxicity.